Edith Steins’s Philosophy: Implications for a Direct Functional Model of Empathy - Flores, Eileen Pfeiffer; Rogoski, Bianca da Nóbrega (Perspectivas em Análise do Comportamento, 2023)
We define empathy, broadly, as understanding another person’s experience. We begin by describing Edith Stein’s phenomenological analysis of empathy. We argue for the continuing relevance of her critique of theories of empathy that presuppose the need for inferences from the “internal” to the “external” and show how mainstream psychological descriptions of empathy based on such assumptions have led to conceptual confusion and, ultimately, to deviance from the phenomenon of interest. We tease out the implicit account of empathy in Skinner’s hypotheses about how we learn to describe private events. We argue that this account is characterized by a lingering inner-outer dualism that leads to incoherence when taken to its ultimate consequences. We propose an alternative conceptualization of empathy, the Direct Functional Model, with three principles: (1) primary givenness of experience, (2) priority of the whole, and (3) interaction. We argue that the model avoids the pitfalls of internal-external dualism and offers an account consistent with the philosophy of Radical Behaviorism.